Influence of Brazilian jiu-jitsu belt graduations on the performance of elite female combat athletes - Dos Santos, M. A. F.; De Albuquerque Maurício, C.; Soto, D. A. S.; Aedo-Muñoz, E.; Brito, C. J.; Pierantozzi, E.; Miarka, B. (Polish Journal of Sport and Tourism, 2024)
Introduction. In Brazilian Jiu-jitsu (BJJ), match durations are determined by belt rank according to the rules. However, a detailed understanding of the dynamics in female matches across belt levels is lacking. Gaining this insight could refine training, better meeting the needs of female athletes at each progression stage. Therefore, this study aims to conduct a comparative time-motion analysis of combat phases among elite female practitioners across different belt ranks.